Challenges of social sustainability: Supply chain management perspective - Halili, Munira; Fernando, Yudi (Inderscience Enterprises Ltd., 2022)
Social sustainability has become an emerging issue due to the firm response to society and is a vital enabler to remaining competitive. However, there is less evidence on how social issues can be solved through sustainable social supply chains. Therefore, it is critical to understand social domain challenges raise in manufacturing firms. This study aims to conceptualise social sustainability drivers to overcome social challenges. The study has explored the social impact and issues using a critical review technique. The results found five drivers for firms to adopt social sustainability practices and highlight the ethical concern. The issues have been discussed, with foresight solutions focused on improving the performance of firms in responding to societal challenges. From a practical perspective, these findings are crucial because they have implications for firms seeking to develop a sustainable social supply chain in achieving a competitive edge.